A method for preparing high-transmittance poly

By using nitrous oxide, silane, hydrogen and phosphane for nitrogen doping deposition on the back of the TOPCon solar cell, a high light transmittance poly was prepared, which solved the problem of high modification costs caused by the lack of carbon dioxide pipelines in the prior art, and achieved the goal of realizing the The same performance and lower production costs as traditional carbon doping poly.

CN119277841BActive Publication Date: 2025-02-25宜宾英发德耀科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411775824.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-02-25
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The poly layer of the existing TOPCon solar cells is deposited by the PECVD/LPCVD method. Although it has the advantages of high yield and fast film formation speed, due to the lack of carbon dioxide pipelines, the use of carbon dioxide doping requires additional modification costs.

Method used

Using a high light transmittance poly preparation method, by putting silicon wafers in a graphite boat and forming a tunnel oxide layer in a quartz tube, then passing nitrous oxide, silane, hydrogen and phosphane for nitrogen doping Deposition leads to obtain nitrogen-doped highly transmissive poly.

Benefits of technology

This method can achieve the same conversion efficiency and conductivity as traditional carbon doped poly without changing the existing equipment, reducing machine transformation costs and improving production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119277841B_ABST
    Figure CN119277841B_ABST
Patent Text Reader

Abstract

The present application proposes a method for preparing high-transmittance poly, which relates to the field of TOPCon battery technology. The method for preparing high-transmittance poly includes the following steps: take an alkali-polished silicon wafer, put it into a graphite boat, and then put it into a quartz tube, and close the furnace door; evacuate and heat it once, introduce nitrous oxide, and generate a tunneling oxide layer on the polished surface of the silicon wafer; evacuate again, introduce silane, nitrous oxide, hydrogen and phosphine, and dope and deposit on the tunneling oxide layer; finally, introduce silane, nitrous oxide, hydrogen and phosphine for re-deposition to obtain nitrogen-doped high-transmittance poly. The present application uses nitrous oxide to provide nitrogen elements for the doping deposition process, and its effect can achieve the same conversion efficiency as the traditional carbon-doping process, and has obvious poly transmittance and conductivity. The nitrogen-doping process of the present application uses the equipment's own nitrous oxide pipeline, and no additional changes and equipment are required, which saves the cost of machine modification compared to traditional carbon-doped poly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of TOPCon cells, and in particular to a method for preparing a high-transmittance poly. Background Art

[0002] TOPCon cells are a type of photovoltaic crystalline silicon cells. In recent years, they have been gradually adopted by industry companies due to their obvious advantages such as high conversion efficiency, low attenuation performance, and high mass production cost performance. TOPCon cells are a type of tunneling oxide passivated contact solar cell, mostly based on N-type silicon. It achieves efficient passivation of the entire back surface through a stacked structure of high-quality ultra-thin silicon oxide and heavily doped polycrystalline silicon, and carriers are selectively collected. This design gives TOPCon cells the advantages of simple preparation process, no light-induced attenuation problems, and is compatible with traditional high-temperature sintering technology.

[0003] TOPCon's back passivation contact structure provides good surface passivation for the back of the silicon wafer. The ultra-thin oxide layer allows the majority carriers (electrons) to tunnel into the polysilicon layer while blocking the minority carriers (holes) from recombination. The majority carriers are then transported laterally in the polysilicon layer and collected by the metal, which greatly reduces the metal contact recombination current and improves the open circuit voltage and short circuit current of the battery. At present, the back of TOPCon solar cells mostly use PECVD / LPCVD to deposit the poly layer. Due to the advantages of less plating, high yield, fast film formation speed, high doping efficiency, and low quartz device loss, PECVD technology is widely used in TOPCon solar cell production. Modifying poly by element doping can reduce the light absorption of polysilicon and improve the light transmittance of polysilicon. Carbon-doped poly has lower resistivity and better conductivity. Carbon dioxide is usually used on the market to provide the carbon element required for doping, but the existing pepoly machine does not have a carbon dioxide pipeline. If carbon dioxide doping is used, additional modification costs need to be invested to modify the gas path of the existing machine. Summary of the invention

[0004] The purpose of the present application is to provide a method for preparing high-transmittance poly. The nitrogen-doped poly prepared by this preparation method has the same effect and lower cost compared with the traditional carbon-doping process.

[0005] In order to solve the above technical problems, the technical solution adopted in this application is:

[0006] The present application provides a method for preparing a highly transparent poly, comprising the following steps:

[0007] S1. Take the alkali-polished silicon wafer, put it into a graphite boat, then into a quartz tube, and close the furnace door;

[0008] S2, evacuating the vacuum and heating up, introducing nitrous oxide, and forming a tunneling oxide layer on the polished surface of the silicon wafer;

[0009] S3, evacuate the air again, introduce silane, nitrous oxide, hydrogen and phosphine, and deposit doping on the tunnel oxide layer;

[0010] S4. Finally, silane, nitrous oxide, hydrogen and phosphine are introduced for re-deposition to obtain nitrogen-doped high-transmittance poly.

[0011] Preferably, the pressure of nitrous oxide introduced in step S2 is 1600-2200 mottr, the temperature is 410-440°C, and the flow rate of nitrous oxide is 9000-12000 sccm / s.

[0012] Preferably, the thickness of the tunneling oxide layer in step S2 is 1.3-1.7 nm.

[0013] Preferably, the pressure in step S3 is 2900-3300 mottr and the temperature is 410-440°C.

[0014] Preferably, in step S3, the flow rate of silane is 2800-3200 sccm / s, the flow rate of nitrous oxide is 150-220 sccm / s, the flow rate of hydrogen is 9000-11000 sccm / s, and the flow rate of phosphine is 300-330 sccm / s.

[0015] Preferably, the doping deposition process in step S3 is to deposit for 80-100s under the conditions of RF power of 14500w and duty cycle of 40 / 400.

[0016] Preferably, the pressure in step S4 is 2900-3300 mottr and the temperature is 410-440°C.

[0017] Preferably, in step S4, the flow rate of silane is 2800-3200 sccm / s, the flow rate of nitrous oxide is 150-220 sccm / s, the flow rate of hydrogen is 9000-11000 sccm / s, and the flow rate of phosphine is 680-750 sccm / s.

[0018] Preferably, the re-deposition in S4 is specifically carried out under the conditions of RF power of 14500W and duty cycle of 40 / 400 for 380-420s.

[0019] Preferably, the thickness of the nitrogen-doped high-transmittance poly modified in step S4 is 90-110 nm.

[0020] Compared with the prior art, the embodiments of the present application have at least the following advantages or beneficial effects:

[0021] 1. In the doping deposition process, nitrous oxide is added to the present application. The ionization of nitrous oxide provides nitrogen elements. Nitrogen enters the deposited poly silicon to change its optical band gap, thereby improving the light absorption in the infrared band and obtaining highly transmittance poly. Compared with the traditional carbon-doped poly, the nitrogen-doped poly of the present application can achieve the same conversion efficiency, has obvious poly transmittance and conductivity, and reaches the qualified level.

[0022] 2. The nitrogen doping process of this application uses the equipment's own nitrous oxide pipeline, without the need for additional modifications and equipment. Compared with traditional carbon-doped poly, it saves the cost of machine modification and increases profits for the factory. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 This is a comparison chart of the external quantum efficiency of nitrogen-doped poly, carbon-doped poly and blank group samples in Experimental Example 1 of this application;

[0025] Figure 2 This is a comparison chart of the contact resistance test of nitrogen-doped poly, carbon-doped poly and blank group samples in Experimental Example 2 of this application. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0027] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to specific embodiments.

[0028] A method for preparing highly transparent poly comprises the following steps:

[0029] S1. Take the alkali-polished silicon wafer, put it into a graphite boat, then into a quartz tube, and close the furnace door;

[0030] S2, evacuating the vacuum and heating up, introducing nitrous oxide, and forming a tunneling oxide layer on the polished surface of the silicon wafer;

[0031] S3, evacuate the air again, introduce silane, nitrous oxide, hydrogen and phosphine, and deposit doping on the tunnel oxide layer;

[0032] S4. Finally, silane, nitrous oxide, hydrogen and phosphine are introduced for re-deposition to obtain nitrogen-doped high-transmittance poly.

[0033] In some embodiments of the present application, the pressure of the nitrous oxide introduced in the above step S2 is 1600-2200 mottr, the temperature is 410-440°C, and the flow rate of the nitrous oxide is 9000-12000 sccm / s.

[0034] In some embodiments of the present application, the thickness of the tunnel oxide layer in the above step S2 is 1.3-1.7 nm.

[0035] In some embodiments of the present application, the pressure of the above step S3 is 2900-3300 mottr, and the temperature is 410-440°C.

[0036] In some embodiments of the present application, in the above-mentioned step S3, the flow rate of silane is 2800-3200 sccm / s, the flow rate of nitrous oxide is 150-220 sccm / s, the flow rate of hydrogen is 9000-11000 sccm / s, and the flow rate of phosphine is 300-330 sccm / s.

[0037] In some embodiments of the present application, the doping deposition process in step S3 is specifically to deposit for 80-100s under the conditions of RF power of 14500w and duty cycle of 40 / 400.

[0038] In some embodiments of the present application, the pressure of the above-mentioned step S4 is 2900-3300 mottr, and the temperature is 410-440°C.

[0039] In some embodiments of the present application, in the above-mentioned step S4, the flow rate of silane is 2800-3200 sccm / s, the flow rate of nitrous oxide is 150-220 sccm / s, the flow rate of hydrogen is 9000-11000 sccm / s, and the flow rate of phosphine is 680-750 sccm / s.

[0040] In some embodiments of the present application, the above-mentioned re-deposition is specifically deposited for 380-420s under the conditions of RF power of 14500w and duty cycle of 40 / 400.

[0041] In some embodiments of the present application, the thickness of the nitrogen-doped high-transmittance poly is 90-110 nm.

[0042] The features and performance of the present application are further described in detail below in conjunction with the embodiments.

[0043] Example 1

[0044] A method for preparing high-transmittance poly comprises the following steps: taking a normally prepared alkali-polished silicon wafer, placing the silicon wafer into a graphite boat using an automated device in a PEPO process, opening a furnace door to place the silicon wafer into a quartz tube, closing the furnace door, evacuating, and heating to 420° C. after leak detection, introducing 10,000 sccm / s of nitrous oxide at a pressure of 2,000 mottr to generate a 1.5 nm tunneling oxide layer on the polished surface, then evacuating, introducing 3,000 sccm / s of silane at a pressure of 3,200 mottr, and introducing 180 sccm / s of monoxide. Dinitrogen, 10000sccm / s hydrogen, 310sccm / s phosphine were deposited for 90s at an RF power of 14500W and a duty cycle of 40 / 400, and then the pressure of 3200mottr was maintained unchanged, 3100sccm / s silane, 180sccm / s nitrous oxide, 10000sccm / s hydrogen, and 720sccm / s phosphine were introduced, and deposited for 400s at an RF power of 14500W and a duty cycle of 40 / 400 to obtain a nitrogen-doped modified poly with a thickness of 100nm.

[0045] Example 2

[0046] A method for preparing high-transmittance poly comprises the following steps: taking a normally prepared alkali-polished silicon wafer, placing the silicon wafer into a graphite boat using an automated device in a PEPO process, opening a furnace door to place the silicon wafer into a quartz tube, closing the furnace door, evacuating, and heating to 435° C. after leak detection, introducing 10,000 sccm / s of nitrous oxide at a pressure of 2,100 mottr to generate a 1.7 nm tunneling oxide layer on the polished surface, evacuating, introducing 2,900 sccm / s of silane at a pressure of 2,900 mottr, and introducing 180 sccm / s of monoxide at a pressure of 1,000 mottr. Dinitrogen, 9000sccm / s hydrogen, 320sccm / s phosphine were deposited for 100s at an RF power of 14500W and a duty cycle of 40 / 400, and then the pressure of 2900mottr was maintained unchanged, 3100sccm / s silane, 180sccm / s nitrous oxide, 9000sccm / s hydrogen, and 680sccm / s phosphine were introduced, and deposited for 410s at an RF power of 14500W and a duty cycle of 40 / 400 to obtain a nitrogen-doped modified poly with a thickness of 105nm.

[0047] Example 3

[0048] A method for preparing high-transmittance poly comprises the following steps: taking a normally prepared alkali-polished silicon wafer, placing the silicon wafer into a graphite boat using an automated device in a PEPO process, opening a furnace door to place the silicon wafer into a quartz tube, closing the furnace door, evacuating, heating to 415°C after leak detection, introducing 10,000 sccm / s of nitrous oxide at a pressure of 1,800 mottr, generating a 1.7 nm tunneling oxide layer on the polished surface, evacuating, introducing 2,800 sccm / s of silane at a pressure of 2,900 mottr, and introducing 180 sccm / s of monoxide. Nitrogen monoxide, 9000sccm / s hydrogen, 300sccm / s phosphine, are deposited for 85s under the conditions of RF power of 14500W and duty cycle of 40 / 400, and then the pressure of 2900mottr is maintained unchanged, 3200sccm / s silane, 180sccm / s nitrous oxide, 9000sccm / s hydrogen, 680sccm / s phosphine are introduced, and the deposition is carried out for 385s under the conditions of RF power of 14500W and duty cycle of 40 / 400 to obtain nitrogen-doped modified poly with a thickness of 92nm.

[0049] Example 4

[0050] A method for preparing high-transmittance poly comprises the following steps: taking a normally prepared alkali-polished silicon wafer, placing the silicon wafer into a graphite boat using an automated device in a PEPO process, opening a furnace door to place the silicon wafer into a quartz tube, closing the furnace door, evacuating, and heating to 425° C. after leak detection, introducing 9000 sccm / s of nitrous oxide at a pressure of 1850 mottr to generate a 1.7 nm tunneling oxide layer on the polished surface, then evacuating, introducing 2800 sccm / s of silane at a pressure of 3100 mottr, and introducing 180 sccm / s of monoxide at a pressure of 1800 mottr. Dinitrogen, 9000sccm / s hydrogen, 300sccm / s phosphine were deposited for 85s at an RF power of 14500W and a duty cycle of 40 / 400, and then the pressure of 3100mottr was maintained unchanged, 3200sccm / s silane, 180sccm / s nitrous oxide, 9000sccm / s hydrogen, and 735sccm / s phosphine were introduced, and deposited for 400s at an RF power of 14500W and a duty cycle of 40 / 400 to obtain a nitrogen-doped modified poly with a thickness of 105nm.

[0051] Example 5

[0052] A method for preparing high-transmittance poly comprises the following steps: taking a normally prepared alkali-polished silicon wafer, placing the silicon wafer into a graphite boat using an automated device in a PEPO process, opening a furnace door to place the silicon wafer into a quartz tube, closing the furnace door, evacuating, heating to 430°C after leak detection, introducing 9000sccm / s of nitrous oxide at a pressure of 1850mottr, generating a 1.7nm tunneling oxide layer on the polished surface, evacuating, introducing 2800sccm / s of silane at a pressure of 2900mottr, and introducing 170sccm / s of nitrous oxide at a pressure of 170mottr. Nitrogen, 11000sccm / s hydrogen, 300sccm / s phosphine were deposited for 100s at an RF power of 14500W and a duty cycle of 40 / 400, and then the pressure of 2900mottr was maintained unchanged, 3200sccm / s silane, 200sccm / s nitrous oxide, 10000sccm / s hydrogen, and 700sccm / s phosphine were introduced, and deposited for 410s at an RF power of 14500W and a duty cycle of 40 / 400 to obtain a nitrogen-doped modified poly with a thickness of 105nm.

[0053] Example 6

[0054] A method for preparing high-transmittance poly comprises the following steps: taking a normally prepared alkali-polished silicon wafer, placing the silicon wafer into a graphite boat using an automated device in a PEPO process, opening a furnace door to place the silicon wafer into a quartz tube, closing the furnace door, evacuating, and heating to 420° C. after leak detection, introducing 9000 sccm / s of nitrous oxide at a pressure of 2100 mottr to generate a 1.4 nm tunneling oxide layer on the polished surface, and then evacuating, introducing 2900 sccm / s of silane at a pressure of 3000 mottr, and introducing 170 sccm / s of nitrous oxide at a pressure of 170 mottr. Nitrogen, 11000sccm / s hydrogen, 300sccm / s phosphine were deposited for 100s at an RF power of 14500W and a duty cycle of 40 / 400, and then the pressure of 3000mottr was maintained unchanged, 3000sccm / s silane, 210sccm / s nitrous oxide, 10000sccm / s hydrogen, and 700sccm / s phosphine were introduced, and deposited for 415s at an RF power of 14500W and a duty cycle of 40 / 400 to obtain a nitrogen-doped modified poly with a thickness of 110nm.

[0055] Comparative Example

[0056] The difference between this comparative example and Example 1 is that this comparative example adopts conventional carbon-doping modification. The specific process is as follows:

[0057] Take the normally prepared alkali polished silicon wafer, and in the PEPO process, use an automated device to place the silicon wafer into a graphite boat, open the furnace door and place the silicon wafer into a quartz tube, close the furnace door, evacuate, and after leak detection, heat up to 425°C, introduce 9000sccm / s of nitrous oxide at a pressure of 1850mottr, and generate a 1.7nm tunneling oxide layer on the polished surface. Then evacuate, introduce 2800sccm / s of silane, 180sccm / s of carbon dioxide, and 9000sccm at a pressure of 3100mottr. / s of hydrogen, 300sccm / s of phosphine, deposited for 85s under the conditions of RF power of 14500W and duty cycle of 40 / 400, and then maintained at 3100mottr pressure unchanged, 3200sccm / s of silane, 180sccm / s of carbon dioxide, 9000sccm / s of hydrogen, and 735sccm / s of phosphine were introduced, and deposited for 400s under the conditions of RF power of 14500W and duty cycle of 40 / 400 to obtain a carbon-doped modified poly with a thickness of 105nm.

[0058] Experimental Example 1

[0059] In this experimental example, the external quantum efficiency (EQE) of Example 1 and the comparative example product was tested to characterize the location of the current gain (the front surface or the back surface of the battery). In this experimental example, a blank group was used as a control. The specific process of the blank group is as follows: after the silicon wafer enters the quartz tube, the furnace door is closed, vacuum is applied, and the temperature is raised to 425°C after leak detection. 9000sccm / s of nitrous oxide is introduced at a pressure of 1850mottr to generate a 1.7nm tunneling oxide layer on the polished surface. Then, vacuum is applied, 2800sccm / s of silane, 9000sccm / s of hydrogen, and 300sccm / s of phosphine are introduced at a pressure of 3100mottr. Deposition is performed for 85s under the conditions of an RF power of 14500W and a duty cycle of 40 / 400. Then, the pressure of 3100mottr is maintained unchanged, 3200sccm / s of silane, 9000sccm / s of hydrogen, and 735sccm / s of phosphine are introduced. Deposition is performed for 400s under the conditions of an RF power of 14500W and a duty cycle of 40 / 400 to obtain a conventional poly with a thickness of 105nm.

[0060] The external quantum efficiency test results are as follows: Figure 1 shown. Figure 1 The horizontal axis represents the wavelength in nm; the vertical axis is the ratio between the number of charge carriers collected by the solar cell and the number of photons with a given energy irradiated from the outside to the solar cell, with the highest collection being 100% and without units.

[0061] from Figure 1It can be seen that both nitrogen-doped poly and carbon-doped poly show good long-wavelength light response, which indicates that the back light response has increased, and the other processes on the back have not changed. It can be inferred that the effect is the improvement brought by poly. The fluctuations of nitrogen-doped poly and carbon-doped poly are basically the same, indicating that the effect of the nitrogen-doping process in this application is the same as that of the traditional carbon-doping process.

[0062] Experimental Example 2

[0063] In this experimental example, the contact resistance test was performed on the products of Example 1 and the comparative example, and the blank group was used as a control. The process of the blank group was the same as that of Experimental Example 1. The final test results are as follows: Figure 2 shown. Figure 2 The middle vertical axis represents the resistance of the contact point between the gate line and the silicon wafer. Because the two are in contact with one surface, the unit is expressed in Ω / cm 2 .

[0064] from Figure 2 It can be seen that compared with the blank group, the back contact resistance of carbon-doped poly and nitrogen-doped poly has decreased, and both show good conductivity, indicating that the nitrogen-doped poly of this application can be applied to the current TOPCon battery preparation.

[0065] Experimental Example 3

[0066] In this experimental example, the efficiency of the product of Example 1 (nitrogen-doped poly) and the comparative product (carbon-doped poly) was tested, and the data of the blank group products were compared (wherein the difference 1 is the difference between the blank group and the carbon-doped poly, and the difference 2 is the difference between the blank group and the nitrogen-doped poly). The process of the blank group is the same as that of Experimental Example 1, and the results are shown in Table 1.

[0067] Table 1

[0068] Group efficiency / % Open circuit voltage / V Short circuit current / A Fill Factor Series resistance / Ω Parallel resistance / Ω Reverse current / A Blank Group 26.694 0.7381 14.086 85.94 0.000620 948.42 0.0185 Carbon doped poly 26.725 0.7379 14.120 85.86 0.000653 857.34 0.0178 Nitrogen-doped poly 26.729 0.7373 14.120 85.94 0.000643 1062.84 0.0215 Difference 1 0.0312 0.000 0.034 -0.08 0.00003 -91.0798 -0.001 Difference 2 0.0353 -0.001 0.034 0.00 0.00002 114.4216 0.003

[0069] It can be seen from Table 1 that the short-circuit current is significantly different, indicating that the efficiency gain is mainly manifested as current gain, which is the effect of improved poly transmittance and conductivity. The efficiency comparison between carbon-doped poly and nitrogen-doped poly is almost the same, and the impact on the conversion efficiency of the battery is basically the same.

[0070] The difference is that the carbon-doping equipment requires the modification of the machine's own gas circuit and the increase of external gas supply, with a comprehensive cost of about RMB 7,000-9,000 per unit; while the nitrogen-doped poly process of the present application directly uses the equipment's original nitrous oxide pipeline, without the need to modify the machine equipment, thus saving the machine's modification cost, which is of great significance for actual production.

[0071] In summary, the method for preparing a high-transmittance poly according to the embodiment of the present application has the following advantages:

[0072] 1. In the doping deposition process, nitrous oxide is added to the present application. The ionization of nitrous oxide provides nitrogen elements. Nitrogen enters the deposited poly silicon to change its optical band gap, thereby improving the light absorption in the infrared band and obtaining highly transmittance poly. Compared with the traditional carbon-doped poly, the nitrogen-doped poly of the present application can achieve the same conversion efficiency, has obvious poly transmittance and conductivity, and reaches the qualified level.

[0073] 2. The nitrogen doping process of this application uses the equipment's own nitrous oxide pipeline, without the need for additional modifications and equipment. Compared with traditional carbon-doped poly, it saves the cost of machine modification and increases profits for the factory.

[0074] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present application.

Claims

1. A method for preparing highly transparent poly, characterized in that: The following steps are involved: S1. Take the alkali-polished silicon wafer, put it into a graphite boat, then into a quartz tube, and close the furnace door; S2, evacuating the vacuum and heating up, introducing nitrous oxide, and forming a tunneling oxide layer on the polished surface of the silicon wafer; S3, evacuate the air again, introduce silane, nitrous oxide, hydrogen and phosphine, and deposit doping on the tunnel oxide layer; S4. Finally, silane, nitrous oxide, hydrogen and phosphine are introduced for re-deposition to obtain nitrogen-doped high-transmittance poly.

2. The method for preparing a highly transparent poly according to claim 1, characterized in that: In the step S2, the pressure of the nitrous oxide introduced is 1600-2200 mottr, the temperature is 410-440°C, and the flow rate of the nitrous oxide is 9000-12000 sccm / s.

3. The method for preparing a highly transparent poly according to claim 2, characterized in that: The thickness of the tunneling oxide layer in step S2 is 1.3-1.7 nm.

4. The method for preparing a highly transparent poly according to claim 1, characterized in that: The pressure of the S3 step is 2900-3300 mottr, and the temperature is 410-440°C.

5. The method for preparing a highly transparent poly according to claim 4, characterized in that: In the step S3, the flow rate of silane is 2800-3200 sccm / s, the flow rate of nitrous oxide is 150-220 sccm / s, the flow rate of hydrogen is 9000-11000 sccm / s, and the flow rate of phosphine is 300-330 sccm / s.

6. The method for preparing a highly transparent poly according to claim 5, characterized in that: The doping deposition process in step S3 is specifically to deposit for 80-100s under the conditions of RF power of 14500w and duty cycle of 40 / 400.

7. The method for preparing a highly transparent poly according to claim 1, characterized in that: The pressure of the S4 step is 2900-3300 mottr, and the temperature is 410-440°C.

8. The method for preparing a highly transparent poly according to claim 7, characterized in that: In the step S4, the flow rate of silane is 2800-3200 sccm / s, the flow rate of nitrous oxide is 150-220 sccm / s, the flow rate of hydrogen is 9000-11000 sccm / s, and the flow rate of phosphine is 680-750 sccm / s.

9. The method for preparing a highly transparent poly according to claim 8, characterized in that: The re-deposition is specifically carried out for 380-420s under the conditions of RF power of 14500W and duty cycle of 40 / 400.

10. The method for preparing a highly transparent poly according to claim 9, characterized in that: The thickness of the nitrogen-doped high-transmittance poly is 90-110 nm.

Citation Information

Patent Citations

  • Preparation method of battery passivation structure based on PECVD (plasma enhanced chemical vapor deposition) process

    CN117239009A

  • Preparation method of tunneling oxide layer of solar cell

    CN117253944A